Safety and efficacy of Sofosbuvir in end stage kidney disease patient: Case report. - MD, Salwa Mahmoud Elwasif; Foaad, Mohammed Taher; Foaad, Mohammed Taher; MD, Khaled Farouk Eldahshan; Elserwy, Nabil Abdelfadil; Elhadid, Mohamed Ahmed; Abbas, Mohamed Hamed; MD, Ayman Fathi Refaie; MD, Ahmed Farouk Donia; MD, Ayman Maher Nagib (International Journal For Research In Health Sciences And Nursing, 2016)
Objectives: The existing standard of care for chronic hepatitis C virus (HCV) infection includes the use of pegylated interferon and ribavirin as primary components of treatment, with the addition of a direct-acting antiviral therapy. Sofosbuvir, an oral nucleotide inhibitor of the HCV nonstructural protein 5B RNA dependent RNA polymerase enzyme, was recently approved for use in combination with ribavirin and/or pegylated interferon for chronic HCV infection, depending on the genotype. Sofosbuvir is orally administered, and peak plasma concentrations are not affected by food. The drug is renally eliminated and does not require adjustment in mild to moderate renal insufficiency or in any degree of hepatic impairment. Case Report: A 62 yearold lady, presented to our center in view of accidentally discovered high serum creatinine. Diagnosis of end stage renal disease was established by both laboratory and radiological finding. Unfortunately she had hepatitis C virus infection during hemodialysis. She received Sofosbuvir with both early and sustained viral response. Conclusion: We try to use Sofosbuvir in a well educated renal failure patient but we cannot grantee its effect on others. Sofosbuvir is a promising drug, need more researches and randomized controlled trials among end stage renal disease patients.